A Comprehensive Review on the Optimization of the Fused Deposition Modeling Process Parameter for Better Tensile Strength of PLA-Printed Parts. (25th August 2022) - Mengesha Medibew, Tesfaye
Abstract : Fused Deposition Modeling (FDM) is a kind of Additive Manufacturing technology, which can produce complex parts by adding layer-by-layer mold automatically from 3D computer-aided design (CAD) data. Although the FDM process has its obvious merits, a fundamental backward factor of its professional enterprise acceptance is the inadequacy of higher mechanical properties and heavy structure of the manufactured product. For that reason, the properties of the manufactured product by FDM are highly dependent upon the choice of FDM parameters. Several studies are investigated to look at the effect of various FDM process parameters to improve print quality characteristics such as mechanical properties, build time, dimensional accuracy, and surface finish of the manufactured parts with having convenient process parameter settings. However, the progress has been gradual and not well organized because of the complex attributes of the FDM process and conflicting process parameters. This paper aims to comprehensively summarize recent studies of advanced statistical and experimental design techniques for better tensile strength of polylactic acid (PLA)-printed parts, the effect of process parameters on tensile strength, and the existing work on the optimization of process parameters.